China's New Place in a World in Crisis Economic, Geopolitical and Environmental Dimensions - Garnaut, Ross; Song, Ligang; Woo, Wing Thye (ANU Press, 2009)
The world and China's place in it have been transformed over the past year. The pressures for change have come from the most severe global financial crisis ever. The crisis has accelerated China's emergence as a great power. But China and its global partners have yet to think or work through the consequences of its new position for the governance of world affairs. China's New Place in a World in Crisis discusses and provides in-depth analysis of the following questions. How have China's growth prospects been affected by the global crisis? How will the crisis and China's response to it impact China's major domestic issues, such as industrialisation, urbanisation and the reform of the state-owned sector of the economy? How will the crisis and the international community's response to it affect the rapidly emerging new international order? What will be China's, and other major developing countries', new role? Can China and the world find a way of breaking the nexus between economic growth and environmental sustainability - especially on the issue of climate change?